Light regulates SlCOP1-mediated degradation of SlJAF13, a transcription factor essential for anthocyanin biosynthesis in Aft tomato fruit - Cao, Ziqian (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.